Exploring the role of regional capacity in human resource development in Indonesia - Burhanuddin, Burhanuddin; Syufri, Syufri; Asriani, Asriani; Hartawan, Hartawan; Saputra, Aco N. (Frontiers in Political Science, 2024)
The role of local government in regional development planning is an essential topic in the context of sustainable local development. This study aimed to analyze the role of local governments in regional development planning and their impact on the effectiveness and sustainability of development at the local level. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis related to regional development policies and regulations. This research was conducted in several districts/cities in certain regions, considering diverse geographical, social, and economic contexts. The results showed that the role of local governments in regional development planning is vital in coordinating various interests, resources, and related actors. Local governments act as regulators, facilitators, and implementers in determining the direction, policies, and allocation of development resources. In addition, community and private-sector involvement is also recognized as an integral part of democratic and inclusive planning processes. The impact of the role of local governments in regional development planning can be seen in increasing the effectiveness of development programs, increasing community participation, reducing regional disparities, and improving the community’s quality of life. Nevertheless, challenges such as corruption, lack of interagency coordination, and political uncertainty remain obstacles that must be overcome. This study concludes that the role of local governments in regional development planning is a critical factor in achieving sustainable regional development. Therefore, measures are needed to strengthen institutional capacity, increase transparency, and strengthen public participation to ensure sustainable and inclusive development planning at the local level.